Disease perception, impacts and coping strategies for onchocerciasis in Southeast Nigeria: a qualitative study among patients and program managers - Adah E. Otache; Ifeyinwa L. Ezenwosu; Edmund N. Ossai; Emmanuel A. Nwobi; Stephen O. Abah; Benjamin SC. Uzochukwu (BMC, 2023)
Abstract Background Onchocerciasis is a disease of public health concern due to the devastating consequences of the disease which impacts negatively on the lives of the people. The negative impact of the disease may affect its perception and lead to the adoption of some coping strategies. Therefore, understanding the disease perception, impacts and coping strategies used by onchocerciasis patients will help plan health interventions aimed at improving their general well-being. Methods This was a community-based study that employed a qualitative method through Key informant interviews (KII) with program managers and focus group discussions (FGD) among people who had Onchocerciasis. Four sessions of FGDs with a total of thirty-two (32) participants and eleven KIIs were conducted to ascertain their in-depth experience in five thematic areas. Results In these communities, onchocerciasis is perceived to have been caused mainly by the bite of blackflies. Other presumed causes by the patients included drinking polluted water, poor environmental sanitation and witchcraft. The disease had a significant detrimental influence on both the physical and financial aspects of life with limited emotional and social impacts. The long-term clinical manifestations of onchocerciasis triggered pain and insufficient mobility. Thus, onchocerciasis patients experienced impairment in normal daily life activities (farming, etc.), dependency, depression and inability to participate in social events. These manifestations stimulated various coping strategies, mainly, nodulectomy by traditional healers. Others included self-medication, taking an overdose of ivermectin, and the use of alcohol. Conclusion Misconceptions about the cause of onchocerciasis still exist among people with the disease. The consequences of the disease impact negatively on various aspects of their lives and stimulate various coping strategies. Therefore, health promotion messages to the public should aim at dispelling misconceptions about the disease and promote healthy coping strategies.